2018
DOI: 10.1055/a-0644-2723
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antimalarial and Antitrypanosomal Activity of Strychnogucine B, a Bisindole Alkaloid from Strychnos icaja

Abstract: Strychnogucine B is a bisindole alkaloid previously isolated from that possesses promising antiplasmodial properties. This compound was synthesized in four steps from (-)-strychnine. As no acute toxicity was observed at the highest tested cumulative dose of 60 mg/kg, its antimalarial activity was determined intraperitoneally at 30 mg/kg/d in a murine model. In the Peters's 4-d suppressive test, this alkaloid suppressed the parasitaemia by almost 36% on day 5 and 60% on day 7 compared to vehicle-treated mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…[45] Moreover, these two bisindole alkaloids (CC 50 pressed the parasitaemia by 60% on Day 7 compared with vehicletreated mice) in a P. berghei murine model. [46][47][48] Moreover, no acute toxicity was observed at the dose of 60 mg/kg, implying its excellent safety profile.…”
Section: Indole Alkaloidsmentioning
confidence: 93%
See 1 more Smart Citation
“…[45] Moreover, these two bisindole alkaloids (CC 50 pressed the parasitaemia by 60% on Day 7 compared with vehicletreated mice) in a P. berghei murine model. [46][47][48] Moreover, no acute toxicity was observed at the dose of 60 mg/kg, implying its excellent safety profile.…”
Section: Indole Alkaloidsmentioning
confidence: 93%
“…Strychnogucine B ( 14 ), a bisindole alkaloid previously isolated from Strychnos icaja , not only showed strong in vitro antiplasmodial activity against FCA 20, FCB1‐R, and W2 strain of P. falciparum with IC 50 values of 85–617 nM, but also demonstrated promising in vivo potency (30 mg·kg −1 ·day −1 , intraperitoneally administrated, suppressed the parasitaemia by 60% on Day 7 compared with vehicle‐treated mice) in a P. berghei murine model. [ 46–48 ] Moreover, no acute toxicity was observed at the dose of 60 mg/kg, implying its excellent safety profile.…”
Section: Indole Alkaloidsmentioning
confidence: 99%
“…Lusakibanza M et al [13] have also shown that the methanolic and dichloromethane extracts of the root bark had a very good selectivity index on falciparum strains. In addition to this interesting antimalarial activity, it showed moderate in vitro antitrypanosomal activit [14]. We know that free radicals are responsible for degenerative diseases like Alzheimer and Parkinson's or chronic diseases like diabetes, cancer, inflammatory diseases.…”
Section: Introductionmentioning
confidence: 97%
“…S. icaja is an African species used as an arrow poison and to treat malaria in Congo, Cameroun and Gabon. Previous studies in our laboratory highlighted the presence of different alkaloids, like isosungucine, strychnogucine B and strychnobaillonine and their antiplasmodial and antimalarial activities (Beaufay et al, 2018;Tchinda et al, 2014). S. mattogrossensis is a South American species growing in the tropical forest of the Amazon.…”
mentioning
confidence: 98%
“…Up to date, the therapy of the SARS-CoV-2 is limited to treat the symptoms and not to cure the Covid-19 disease (like Tamiflu for influenza), for this reason, the discovery of new antivirals is crucial.Natural products are an important source of antiviral compounds and therefore are extensively studied (Kim, 2021).Broad studies in our laboratory on Asian, African and Brazilian Strychnos species have been conducted, and have led to the isolation of numerous alkaloidic compounds. These plants have been evaluatedfor their antimalarial and cytotoxic potentials (Beaufay et al, 2018;…”
mentioning
confidence: 99%